Measuring Basal Force Fluctuations of Debris Flows Using Seismic Recordings and Empirical Green's Functions. Issue 9 (7th September 2020) - Allstadt, Kate E.; Farin, Maxime; Iverson, Richard M.; Obryk, Maciej K.; Kean, Jason W.; Tsai, Victor C.; Rapstine, Thomas D.; Logan, Matthew
Abstract: We present a novel method for measuring the fluctuating basal normal and shear stresses of debris flows by using along‐channel seismic recordings. Our method couples a simple parameterization of a debris flow as a seismic source with direct measurements of seismic path effects using empirical Green's functions generated with a force hammer. We test this method using two large‐scale (8 and 10 m 3 ) experimental flows at the U.S. Geological Survey debris‐flow flume that were recorded by dozens of three‐component seismic sensors. The seismically derived basal stress fluctuations compare well in amplitude and timing to independent force plate measurements within the valid frequency range (15–50 Hz). We show that although the high‐frequency seismic signals provide band‐limited forcing information, there are systematic relations between the fluctuating stresses and independently measured flow properties, especially mean basal shear stress and flow thickness. However, none of the relationships are simple, and since the flow properties also correlate with one another, we cannot isolate a single factor that relates in a simple way to the fluctuating forces. Nevertheless, our observations, most notably the gradually declining ratio of fluctuating to mean basal stresses during flow passage and the distinctive behavior of the coarse, unsaturated flow front, imply that flow style may be a primary control on the conversion of translational to vibrational kinetic energy. This conversion ultimately controls the radiation of high‐frequency seismic waves. Thus, flow style may provide the key to revealing the nature of the relationship between fluctuating forces and other flow properties. Key Points: We use empirical Green's functions to measure the spatiotemporal evolution of debris‐flow basal force fluctuations from seismic records Seismically derived basal force fluctuation estimates of large‐scale experimental debris flows match independent force plate measurements Basal force fluctuations correlate strongly but nonlinearly with flow characteristics, especially mean basal forces and flow thickness